Pengembangan dan Pengolahan Ikan Tongkol (Euthynnus affinis) Dengan Kombinasi Sayuran Lokal yang Berpotensi Mencegah dan Mengendalikan Stunting pada Masyarakat Desa Bakipandeyan - Novena Yety Lindawati; Ovikariani Ovikariani; Luthfi Nur Athifa; Putu Tia Angelia; Rinda Susan Yuliyani; Arfi Delasafira (Jurnal Surya Masyarakat, 2024)
Stunting is the condition of toddlers who experience failure to grow or have a body condition that is shorter than their age standard due to malnutrition, inadequate recurrent infections in the first 1,000 days of life. Bakipandeyan Village, Baki, Sukoharjo is one of the assisted villages that pays attention to the prevention and control of stunting. This encourages the holding of community service activities aimed at preventing and controlling stunting in children aged 0-24 months. This activity program uses seminar and workshop methods directly to mothers with children aged 0-24 months, health workers, and PKK cadres by considering the status of stunting and malnutrition in the Bakipandeyan village area, Baki, Sukoharjo. The results of community service showed an increase in participants' knowledge which was evaluated through an average increase in pretest scores from 79.77 to 93.86 at posttest as well as an increase in participants' skills in workshop activities. The results of the partner satisfaction questionnaire showed that people who gave good to very good appreciation reached 95%, so this activity was appropriate, satisfying and accepted by the people of Bakipandeyan Village, Baki, Sukoharjo.